A Case of Typhoid Fever with Hepatic Granulomas and Enteritis - Shraddha Narechania; Marc Duran; Vidhya Karivedu; K. V. Gopalakrishna (Case Reports in Pathology)
The common histopathologic hepatic manifestations in patients infected with Salmonella include cloudy swelling and balloon degeneration with vacuolation of the hepatocytes and steatosis. Hepatic granulomas are a very rare finding, so far reported in very few cases. We report a 64-year-old patient with Salmonella enteritis who was found to have multiple 1.4 to 1.6 cm hypoechoic liver masses on ultrasound of the abdomen which on biopsy revealed hepatic granulomas. This case highlights the importance of keeping the differential diagnosis of Salmonella typhi (S. typhi) in mind in a patient with hepatic granulomas.